Перспективи розвитку інформаційної структури музеїв - Мина, Жанна (Видавництво Львівської політехніки, 2012)
This article analyzes the problem of information structure of museums. Museums as keepers of cultural objects and works of art require information support and bright advertisement. The use of computer technology, the Internet – one of the most effective ways to address these problems. Taking care of your own image, in museums created web-pages with detailed information of exposition.
Keywords: музей; комп’ютерні технології; web-сторінка; мережі Internet; системи обліку і зберігання; музейний об’єкт